Clear Cell Sarcoma of the Neck Which Metastasized to the Mammary Gland - Ippei Fukada; Seiichiro Nishimura; Masahiko Tanabe; Hidetomo Morizono; Masujiro Makita; Naoya Gomi; Rie Horii; Futoshi Akiyama; Takuji Iwase (Case Reports in Oncology, 2013)
Malignant neoplasms very rarely metastasize to the mammary gland, the incidence of which is reported as 0.5–2%. Clear cell sarcoma is a rare neoplasm, accounting for approximately 1% of all soft tissue tumors, which commonly occurs in the distal extremities of young adults aged approximately 20 to 40 years. So it is also called malignant melanoma of soft parts because it frequently produces melanin. We report a case of a 26-year-old woman who presented with a neck mass. The mass was surgically removed, and pathological diagnosis was clear cell sarcoma of the neck, harboring the EWS-ATF1 chimeric gene. Computed tomography detected a right breast mass 11 months after operation. She was referred to our department, and the right breast tumor was resected. Histopathological examination revealed a 2.5-cm, well-defined mass composed of nests of small, spindle-shaped tumor cells with abundant, clear cytoplasm containing round nuclei and prominent nucleoli. The tumor cells were immunohistochemically positive for HMB45, S-100, and Melan-A. These findings led to a diagnosis of metastasis of clear cell sarcoma to the mammary gland. This is the first report of clear cell sarcoma of the neck which metastasized to the mammary gland.